The Mechanism and Modelling of Shunt Current in the Vanadium Redox Flow Battery. Issue 10 (5th July 2016) - Skyllas‐Kazacos, Maria; McCann, John; Li, Yifeng; Bao, Jie; Tang, Ao
Abstract: To date, no physical model has been proposed to describe the mechanism of shunt currents in bipolar electrochemical reactors with a common electrolyte manifold. In this paper, we show that under the influence of the cell voltage driving force, the bipolar electrode provides an internal electrical pathway that allows electrons to flow from the negative half‐cell of one cell, to the positive half‐cell of the adjacent cell, leading to self‐discharge reactions that can occur even when the stack is at open‐circuit. This is made possible, by the presence of the interconnecting channels and common electrolyte manifolds that enable the flow of hydrogen or other charge carrying ions to complete the circuit. The larger the number of cells in the cell stack, the larger the number of internal pathways for electrons and protons to flow, so the greater the shunt current losses. Abstract : A physical model describing the mechanism of shunt currents in electrochemical bipolar reactors that employ parallel hydraulic flow through common manifolds is presented for the first time. Internal self‐discharge reactions associated with shunt current occur in the positive half of one cell and the negative half of adjacent cells with electrons flowing through the bipolar electrode. Mathematical modelling and simulations are presented to demonstrate the effect of manifold and channel dimensions on coulombic efficiency.